Soil carbon, nitrogen and phosphorus distribution in grassland systems, important for landscape and environment - Šlepetienė, Alvyra; Liaudanskienė, Inga; Šlepetys, Jonas; Stukonis, Vaclovas; Jokubauskaitė, Ieva (Journal of Environmental Engineering and Landscape Management, 2013)
The accumulation of organic carbon (SOC), nitrogen (N) and phosphorus (P) in the soils of protected areas and agrarian lands in Central Lithuania was assessed. Wood pasture is recognised as an important but now scarce element of the historic environment still evident in the current landscape. Soil pH was lower in the surviving wood pasture compared to the pasture under restoration, and pH of the old semi-natural pasture and organically grown legume sward soils was close to neutral. The highest SOC content was accumulated in the meadows of pre-mainland section of floodplain of the Nevėžis. It was more than 5 times as high as that in agrarian land grown with swards, and higher than that accumulated in semi-natural pasture and wood pasture. Soils of the protected areas of pre-mainland section were characterized by the largest amount of N. Soils of semi-natural pasture, affected by agricultural management, and meadows of pre-mainland section were found to be the highest in the total P content. Due to the differences in agricultural management, diverse plant communities are developing in the central section of floodplain of the middle reaches of the Nevėžis.